2010
DOI: 10.1177/0192623309356448
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Toxicology Approaches for Small Molecule Oncology Drugs

Abstract: A daunting, unmet medical need exists for effective oncology chemotherapies, with cancer deaths in 2009 to exceed 560,000 in the United States alone. Because of the rapid demise of the majority of cancer patients with metastatic disease, oncology drug development must follow a much different paradigm than therapeutic candidates for less onerous diseases. The majority of drug candidates in development today are targeted at cancer therapy. Many of these candidate chemotherapeutic agents are active against novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 62 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…1–4 It is not uncommon for candidates to pass this screening process successfully only to exhibit poor specificity, solubility and distribution in vivo . 59 Such failures, deep in the clinical testing process, results in tremendous research and development costs that are ultimately passed on to consumers through the limited number of drugs that do make it to the market. It is possible to lower the costs of development for promising drug agents to the clinical trial phase by creating drug formulations that improve efficacy and reduce side effects through targeted delivery.…”
Section: Introductionmentioning
confidence: 99%
“…1–4 It is not uncommon for candidates to pass this screening process successfully only to exhibit poor specificity, solubility and distribution in vivo . 59 Such failures, deep in the clinical testing process, results in tremendous research and development costs that are ultimately passed on to consumers through the limited number of drugs that do make it to the market. It is possible to lower the costs of development for promising drug agents to the clinical trial phase by creating drug formulations that improve efficacy and reduce side effects through targeted delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these filters are based on empirical rules targeting several pharmacokinetic indices that confer crucial information for the speed and success in drug discovery. Herein, we predicted for carvacrol thirteen of the most crucial drug-likeness filters recommended during the design of cancer drug candidates [ 35 , 36 ], which are shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to evaluate different drug discovery strategies, it was observed that the percentage of newly approved small molecule drugs with a novel molecular mechanism of action is less than 20 % of the total approvals during the study duration considered [ 2 ]. Currently, the majority of drug candidates are aimed at cancer treatment and are therefore studied for activity at multiple, possibly novel biological targets, presenting a high probability of multiple unique toxicological profiles [ 3 ]. Therefore, it is essential to employ novel strategies that can predict the fate of the chemicals in early stages of development to overcome the failure rates and accelerate the development and approval of promising candidates.…”
Section: Introductionmentioning
confidence: 99%